OP0130 PREMATURE OVARIAN FAILURE IN PATIENTS AFFECTED BY SYSTEMIC LUPUS ERYTHEMATOSUS: A CROSS-SECTIONAL CASE CONTROL STUDY. (June 2019) - Orefice, Valeria; Ceccarelli, Fulvia; Perrone, Giuseppina; Pirone, Carmelo; Perricone, Carlo; Truglia, Simona; Miranda, Francesca; Pacucci, Viviana Antonella; Spinelli, Francesca; Galoppi, Paola; Alessandri, Cristiano; Valesini, Guido; et al.
Abstract : Background: Women suffering from autoimmune diseases, such as Systemic Lupus Erythematosus (SLE), could develop menopause at a younger age in comparison with healthy population. In particular, a higher frequency of abnormal ovarian function has been described in SLE cohorts 1-4 . The presence of a cause-effect link between the disease and such modifications remains poorly understood. The role of disease activity and chronic damage, combined with the intake of some drugs, such as cyclophosphamide (CYC), has been suggested 2 . Objectives: We evaluated the age at natural menopause and the prevalence of premature ovarian failure (POF) in a monocentric Caucasian SLE cohort. Additionally, we analyzed the possible association with the disease features. Methods: We performed a cross-sectional case-control study, enrolling consecutive SLE women and reporting their clinical and laboratory data. As control group (healthy controls - HC), women without autoimmune diseases were enrolled. By using an interview, gynecological characteristics were investigated in patients and controls: in particular, we registered age at menarche, occurrence and age of menopause, history of hysterectomy. Natural menopause was defined as the absence of menses for at least 12 months in women aged ≥40 years and POF as amenorrhea of at least 12 months in women < 40 years. Results: We enrolled 196 Caucasian women with SLE (median age 47.0 years, IQR 16.7; median disease duration 132 months, IQR 180) and 90 HC (median age 49.9 years, IQR 15.0). Ninety-four SLE patients (48.0%) and 26 HC (23.4%) referred a condition of menopause: the median age at occurrence was significantly lower in SLE than HC (47 years, IQR 8.0 versus 50.5 years, IQR 4; P=0.0001). Among the SLE patients, a natural menopause was observed in 70 subjects (74.4%), surgical in 7 (7.4%), iatrogenic in 17 (18.1%). In particular, 13 (13.8%) SLE patients referred the occurrence of menopause after CYC exposure. Excluding SLE patients with surgical menopause, we registered POF in 16 patients (17%); this prevalence was significantly higher in comparison with HC group, in which none of subjects experienced POF (P=0.0001). The comparison between SLE patients developing POF and those with natural menopause history demonstrated a significant higher prevalence of anti-Sm (31.2% versus 10.2%; P=0.0004), anti-RNP (25.0% versus 12.8%; P=0.02), anti-cardiolipin (aCL) IgG/IgM (50.0% versus 26.9%; P=0.0008) and lupus anticoagulant (37.5% versus 17.9%; P=0.002). As expected, a significant more frequent CYC treatment was identified in patients developing POF (56.0% versus 11.0%; P=0.0001). Moreover, POF subjects showed a significant more frequent history of treatment with azathioprine (62.5% versus 30.7; P=0.0001), mycophenolate mofetil (50% versus 20.5%; P=0.0001) and cyclosporine A (37.5% versus 19.2%; P=007). No significant differences were found in terms of clinical manifestations and mean SLICC/ACR damage index (SDI). Conclusion: In the present study, we observed a significantly lower age at menopause in SLE patients in comparison with HC; in addition, a significantly higher frequency of POF was observed. POF was associated with a more active disease, in terms of autoantibodies prevalence and use of immunosuppressant drugs. Finally, for the first time, it was found an association between POF and antiphospholipid positivity, suggesting a possible role of these antibodies, in particular aCL, in POF development. References: [1] Mayorga J, et al. Lupus 2016 [2] Malheiro, et al. Gynecol Endocrinol 2014 [3] Fatnoon NN, et al. Singapore Med J 2008 [4] Lawrenz, et al. Lupus 2011. Disclosure of Interests: Valeria Orefice: None declared, Fulvia Ceccarelli: None declared, Giuseppina Perrone: None declared, Carmelo Pirone: None declared, Carlo Perricone Speakers bureau: BMS; Lilly, Celgene, Sanofi, Simona Truglia: None declared, Francesca Miranda: None declared, viviana antonella pacucci: None declared, francesca spinelli: None declared, Paola Galoppi: None declared, cristiano alessandri: None declared, Guido Valesini: None declared, fabrizio conti: None declared